Transparent poly(methyl methacrylate-butyl acrylate-hexafluorobutyl methacrylate) for conservation of stone relics synthesis and test - Ma, Chuang; Chin, Sim Yee; Zhang, Yue; Suriati, Ghazali; Zhang, Hengqiang (Walter de Gruyter GmbH, 2024)
A transparent poly(methyl methacrylate-butyl acrylate-hexafluorobutyl methacrylate) stone relics protective material was synthesized using one-pot method. The synthesized polymer was coated on the surface of the stone samples or glass plates. SEM was used to observe the micromorphology of pristine stone and stone covered polymer coating samples. Physical properties of polymer coatings were characterized by FTIR, XRD and TGA-DSC. The conservation properties of polymer coatings were investigated by testing adhesion, transparency, hydrophobicity, mass loss rate and appearance of the simulated stone relics after freeze–thaw, UV irradiation and acid aging processes. Results show that poly (MMA-BA-20.04 %HFMA) outperformed the others with water contact angle remained 108.23°, 109.34° and 106.96° as well as the change of chromaticity difference values of 0.79, 0.02 and 0.08, after freeze-thaw, UV-aging and acid-aging processes, respectively. All these data indicate that the as-synthesized polymer could potentially use in conservating the stone relics due to its superior hydrophobicity, transparency, anti-acid and anti-UV aging properties as well as durability for freeze–thaw.